2020
DOI: 10.7150/ijms.40417
|View full text |Cite
|
Sign up to set email alerts
|

Circulating fatty acid-binding protein 1 (FABP1) and nonalcoholic fatty liver disease in patients with type 2 diabetes mellitus

Abstract: Background: Fatty acid-binding protein 1 (FABP1) (also known as liver-type fatty acid-binding protein or LFABP) is a protein that is mainly expressed in the liver, and is associated with hepatocyte injury in acute transplant rejection. Reduced levels of FABP1 in mice livers have been shown to be effective against nonalcoholic fatty liver disease (NAFLD). In this study, we investigated the association between plasma FABP1 levels and NAFLD in patients with type 2 diabetes mellitus (T2DM). Methods: We enrolled 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…Fatty acid-binding proteins (FABPs) secreted from liver coordinate lipid responses in hepatocytes and link various metabolic and inflammatory pathways which include fatty acid uptake, transport, oxidation, lipid synthesis and storage [82]. Cumulative evidence suggests the positive correlation of FABP-1 with obesity, diabetes and NASH [83,84]. In accordance with previous reports, our results showed increased levels of FABP-1 in patients with obesity and diabetes with or without fatty infiltration.…”
Section: Discussionsupporting
confidence: 91%
“…Fatty acid-binding proteins (FABPs) secreted from liver coordinate lipid responses in hepatocytes and link various metabolic and inflammatory pathways which include fatty acid uptake, transport, oxidation, lipid synthesis and storage [82]. Cumulative evidence suggests the positive correlation of FABP-1 with obesity, diabetes and NASH [83,84]. In accordance with previous reports, our results showed increased levels of FABP-1 in patients with obesity and diabetes with or without fatty infiltration.…”
Section: Discussionsupporting
confidence: 91%
“…After fasting for at least 8 hours, a peripheral blood sample was taken from the worker’s antecubital vein. Complete blood count and serum uric acid, aspartate aminotransferase (AST), alanine aminotransferase (ALT), glucose, HbA1c, and lipid panel (including plasma total cholesterol, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides) were also analyzed during the health check, and were determined in all workers using standard commercial methods with a parallel, multichannel analyzer (Hitachi 7170A, Tokyo, Japan) as described in our previous reports [ 20 , 21 ]. Peripheral leukocyte count was analyzed with an automated cell counter (XE-2100 Hematology Alpha Transportation System, Sysmex Corporation, Kobe, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Studies show that CCR2+ macrophage is a pioneer in the hepatic monocyte uptake; it can induce lipolysis through regulation of epinephrine and norepinephrine levels and promote liver injury [ 78 ]. In T2DM-NAFLD subjects, authors found increased levels of Fatty acid-binding protein 1 (FABP1), a protein that facilitates the storage of FFAs and urges liver damage [ 79 , 80 ]. Some suggested that this protein may be used as a biomarker to detect liver injury [ 81 ].…”
Section: Immunopathogenesismentioning
confidence: 99%